2016
DOI: 10.1007/s11136-016-1462-8
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in long-term survivors of acute lymphoblastic leukemia in childhood and adolescence

Abstract: Overall, long-term survivors of ALL in childhood enjoy good HRQL but some experience appreciable disability, though this is not associated with BMI or, in the main, with physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
3
24
0
1
Order By: Relevance
“…Measures of HRQL were taken from another previous report using the Health Utilities Index, which is a collection of multi‐attribute, preference‐based instruments developed at McMaster University . The Health Utilities Index Mark 2 (HUI2) and the Health Utilities Index Mark 3 (HUI3) are complementary systems.…”
Section: Methodsmentioning
confidence: 99%
“…Measures of HRQL were taken from another previous report using the Health Utilities Index, which is a collection of multi‐attribute, preference‐based instruments developed at McMaster University . The Health Utilities Index Mark 2 (HUI2) and the Health Utilities Index Mark 3 (HUI3) are complementary systems.…”
Section: Methodsmentioning
confidence: 99%
“…We found that total HRQL scores of the ALL survivors appeared to be lower than the expected values for healthy and chronically ill children in the literature [14,15,17]. A strong association between poor HRQL in survivors of pediatric ALL and depression, anxiety, insomnia, pain, and obesity was found in several studies [19,20,21,27,28,29,30]. As a remarkable finding of our study, the scores for physical well-being, emotional well-being, family, and social functioning of the patient and sibling self-reports and parent proxy reports also appeared to be lower than the expected values for healthy and chronically ill child self-reports and their parent proxy reports.…”
Section: Discussionmentioning
confidence: 86%
“…This is exemplified by survivors of acute lymphoblastic leukemia (ALL), a small proportion of whom exhibit notable disabilities in the attributes of hearing, emotion, cognition and pain. 42 In contrast, a study of more than 1000 survivors of cancer in childhood (63% of whom were in the AYA age group) found that those who had had central nervous system (CNS) or bone tumours commonly experienced compromised HRQL. 43 The former have shown progressive decline over a decade of follow-up, in a separate study, even to the point of a negative score, indicative of a self-reported health state worse than being dead.…”
Section: The Added Value Of Promismentioning
confidence: 99%
“…It should be emphasised that while long‐term survivors of cancer in early life, as a group, may have overall HRQL very similar to that of their peers in the general population, the ‘tale may be in the tail’. This is exemplified by survivors of acute lymphoblastic leukemia (ALL), a small proportion of whom exhibit notable disabilities in the attributes of hearing, emotion, cognition and pain . In contrast, a study of more than 1000 survivors of cancer in childhood (63% of whom were in the AYA age group) found that those who had had central nervous system (CNS) or bone tumours commonly experienced compromised HRQL .…”
Section: Usefulness Of Measuring Hrql In Ayas With Cancermentioning
confidence: 99%